How does social context influence appraisal and help‐seeking for potential cancer symptoms in adults aged 50 and over? A qualitative interview study. (21st June 2022) - Adam, Rosalind; Thornton, Alison J.; Whitaker, Katriina L.; Murchie, Peter; Hannaford, Philip C.; Hall, Susan; Smith, Sarah; Elliott, Alison M.
Abstract: Objective: To investigate how social context and social network activation influence appraisal and help‐seeking for symptoms potentially indicative of cancer. Methods: Semi‐structured telephone interview study. Community dwelling adults who had experienced at least one symptom potentially indicative of cancer within the last month were sampled from a national symptom survey. Results: Thirty‐four interviews were conducted. Participants looked to peers and wider society to judge whether symptoms might be normal for their age. Involvement of others in symptom appraisal promoted an active management strategy, such as contacting a healthcare professional or trying a medication. There were practical, emotional, attitudinal, normative and moral barriers to involving others. Cancer narratives from significant others, public health campaigns and the media influenced symptom appraisal. Participants held mental representations of types of people who get cancer, for example, smokers and unfit people. This had two consequences. First, participants did not identify themselves as a candidate for cancer; impeding help‐seeking. Second, social judgements about lifestyle introduced stigma. Conclusion: Involving friends/family in symptom appraisal facilitates help‐seeking but barriers exist to involving others. Campaigns to promote earlier cancer diagnosis should incorporate age‐appropriate narratives, address misconceptions about 'types' of people who get cancer and tackle stigma about lifestyle factors.